An examination of convergent constructs among Level of Service measures and other measures - Jung, Sandy; Daniels, Melissa; Friesen, Michael; Ledi, Denise (My University, 2012)
The Level of Service Inventory-Revised and its successor, the Level of Service/Case Management Inventory are theoretically based risk assessment measures derived from what are known as the “Central Eight” risk factors. These Level of Service instruments have been empirically demonstrated to predict recidivism; however, given the importance of using the these instruments to assess the central eight risk factors, it is also important to ensure that the measures’ subscales are actually assessing the intended constructs. In the present study, files of 219 offenders were coded to investigate the concurrent and discriminant validity by correlating seven of the Level of Service subscales with construct-relevant scales of the Personality Assessment Inventory, Cormier-Lang Criminal History Score, Minnesota Multiphasic Personality Assessment-2, and intelligence measures. The results provide preliminary support for the construct validity of the domains measured by the Level of Service instruments, with the exception of the Emotional/Personal subscale.
Keywords: construct valdity; Level of Service; risk assessment; risk factors